Production of fungal hypocrellin photosensitizers: Exploiting bambusicolous fungi and elicitation strategies in mycelium cultures - Xin Ping Li; Wen Hao Shen; Jian Wen Wang; Li Ping Zheng (Mycology)
Hypocrellins, a group of naturally occurring perylenequinone pigments produced by Shiraia bambusicola, are notable for their potential use in photodynamic therapy (PDT) for treating cancers and viruses. Traditionally, hypocrellins have been extracted from the fruiting bodies of S. bambusicola, a parasitic fungus on bamboo. However, the yield from wild Shiraia fruiting bodies is often insufficient, prompting a shift towards seeking other fungi with higher yields of hypocrellins as alternative sources. This review comprehensively examines the current research on the isolation, identification, and bioactivity of fungal perylenequinones from Shiraia isolates from ascostromata or fruiting bodies, Shiraia-like endophytes, and other endophytes from bamboos. Additionally, the review discusses the culture methods and conditions for solid-state and submerged fermentation of hypocrellin-producing fungi, including medium components, culture conditions, and optimisation of fermentation factors, as mycelium cultures have emerged as a promising alternative for the production of hypocrellins. Furthermore, novel elicitation strategies are presented to address the bottleneck of lower production of hypocrellins in mycelium cultures, focusing on the preparation, characterisation, and application of biotic and abiotic elicitors. This review aims to facilitate further exploration and utilisation of fungal resources and elicitation strategies for enhanced production of hypocrellins in mycelium cultures.